New insights into enterocin CRL35: mechanism of action and immunity revealed by heterologous expression in Escherichia coli - Barraza, Daniela Estefanía (2017)
The role of the class IIa bacteriocin membrane receptor protein remains unclear, and the following two different mechanisms have been proposed: the bacteriocin could interact with the receptor changing it to an open conformation or the receptor might act as an anchor allowing subsequent bacteriocin insertion and membrane disruption. Bacteriocin-producing cells synthesize an immunity protein that forms an inactive bacteriocin–receptor–immunity complex. To better understand the molecular mechanism of enterocin CRL35, the peptide was expressed as the suicidal probe EtpM-enterocin CRL35 in Escherichia coli, a naturally insensitive microorganism since it does not express the receptor. When the bacteriocin is anchored to the periplasmic face of the plasma membrane through the bitopic membrane protein, EtpM, E. coli cells depolarize and die. Moreover, co-expression of the immunity protein prevents the deleterious effect of EtpM-enterocin CRL35. The binding and anchoring of the bacteriocin to the membrane has demonstrated to be a sufficient condition for its membrane insertion. The final step of membrane disruption by EtpM-enterocin CRL35 is independent from the receptor, which means that the mannose PTS might not be involved in the pore structure. In addition, the immunity protein can protect even in the absence of the receptor.